APPLICATION OF THE PANCASILA MODEL IN THE SOURCES OF INDONESIAN STATE LEGAL SYSTEM - Novi Dwi Komala; Dwita Hasanah S; Muhammad Sabil Anugrah (Academic Solution Publisher, 2024)
Pancasila as the foundation of the Indonesian state has a fundamental role in shaping the national legal system. The application of the Pancasila model in the source of the Indonesian state legal system refers to the principles contained in Pancasila which are used as guidelines in making laws and legal practices in Indonesia. In this context, Pancasila not only functions as the basis for ethics or the nation's outlook on life, but also as a source of law that regulates every legal policy, both in the 1945 Constitution of the Republic of Indonesia and in other legal products. This study aims to analyze how the values ​​contained in Pancasila can be applied consistently in the Indonesian state legal system, as well as the challenges faced in the implementation process. Through a qualitative approach and analysis of legal documents, this study found that although Pancasila is the basis for compiling the Indonesian legal system, its application in daily legal practice still faces several obstacles, especially in terms of enforcing the principles of social justice and humanity contained in Pancasila. This study emphasizes the importance of strengthening collective awareness of the values ​​of Pancasila among state officials and society in order to create a more just and prosperous legal system. Therefore, greater efforts are needed to integrate Pancasila values ​​more effectively into every legal policy implemented in Indonesia